2018
DOI: 10.1155/2018/1860513
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Hypertension and Endothelial Dysfunction Is Linked to NADPH Oxidase‐Derived Superoxide Formation in Venous Thrombosis and Pulmonary Embolism in Mice

Abstract: Pulmonary embolism (PE) results from deep vein thrombosis (DVT) and can lead to chronic thromboembolic pulmonary hypertension (CTEPH) involving vascular dysfunction. Mechanisms are incompletely understood, in part due to lack of mouse models. We induced PE in C57BL/6 mice by intravenous injection of thrombin (166 U/kg BW), confirmed by a sudden bradycardia, bradypnea, and an increase in pulmonary artery (PA) pressure observed by high-frequency ultrasound. While symptoms resolved rapidly after single thrombin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
2
26
0
4
Order By: Relevance
“…Even though carfilzomib did not lead to a shift in cellular bioenergetics, it led to a decrease in ATP production via oxidative phosphorylation. Carfilzomib is known to induce a mitochondrial deficit in resistant MM cells in vitro in a mitochondria-derived activator of caspase (SMAC)-Survivin dependent manner leading to increased apoptosis, mitochondrial-derived ROS release and inhibition of mitochondrial respiration, which is in line with our data [ 48 , 49 ]. It should be stressed at this point that the metabolic switch induced by metformin might be of great clinical importance, as drugs that can modulate cellular bioenergetics in a similar manner, are being successfully incorporated in the management of heart failure [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Even though carfilzomib did not lead to a shift in cellular bioenergetics, it led to a decrease in ATP production via oxidative phosphorylation. Carfilzomib is known to induce a mitochondrial deficit in resistant MM cells in vitro in a mitochondria-derived activator of caspase (SMAC)-Survivin dependent manner leading to increased apoptosis, mitochondrial-derived ROS release and inhibition of mitochondrial respiration, which is in line with our data [ 48 , 49 ]. It should be stressed at this point that the metabolic switch induced by metformin might be of great clinical importance, as drugs that can modulate cellular bioenergetics in a similar manner, are being successfully incorporated in the management of heart failure [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…Sections were hematoxylin–eosin and Sirius red stained for histology, as well as for wall thickness and collagen deposition assessment [ 57 ]. For immunofluorescence (IF) experiments aortic sections were snap-frozen in the optimal cutting temperature (OCT) medium (Tissue-Tek ® O.C.T.™ Compound, Fisher Scientific) and sliced in 3 μm cryosections [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NOX–derived reactive oxygen species take part in many kinds of cardiovascular diseases. It has been reported that NADPH oxidase-derived superoxide is present in repetitive pulmonary embolism which leads to pulmonary arterial hypertension [45]. Kuroda et al reported that the NOX4-ROS pathway had been shown to aggravate profibrotic responses, remodeling processes, and worsening cardiac function in the failing heart [46].…”
Section: Discussionmentioning
confidence: 99%
“…Развитие ЛАГ ассоциировано с ремоделированием легочных артерий и нарушением барьерной функции эндотелия. В результате увеличивается продукция провоспалительных цитокинов (фактор некроза опухоли α, интерлейкин 6), что увеличивает экспрессию и активность NADPH-оксидазы и вызывает оксидативный стресс [10].…”
Section: рисунок 2 -зависимость относительного содержания моноцитов оunclassified